The power of feedback and reflection: Testing an online scenario-based learning intervention for student teachers. (August 2021) - Bardach, Lisa; Klassen, Robert M.; Durksen, Tracy L.; Rushby, Jade V.; Bostwick, Keiko C.P.; Sheridan, Lynn
Abstract: Advances in research on educational technologies and increasing access to computers offer teacher education providers numerous tools and opportunities for supporting student teachers. However, systematic investigations of online interventions using complex classroom scenarios (scenario-based learning activities) are currently lacking. This study tested whether an online scenario-based learning activity has a positive impact on student teachers' self-efficacy and emotional, motivational, and cognitive classroom readiness before they start their first teaching practicum. In order to draw differentiated conclusions, we explored whether the effectiveness of the intervention depends on the inclusion of automatized expert teacher feedback and the opportunity to reflect on the scenarios. A total of 238 Australian student teachers (64.3% females, mean age = 23.84 years, SD  = 6.64) participated in the study. The student teachers were randomly assigned to one of three experimental conditions:control group (online scenario-based learning activity), intervention group 1 (online scenario-based learning activity and feedback), and intervention group 2 (online scenario-based learning, feedback, and reflection). The findings indicated that, compared to the control group, both intervention conditions had a significant positive effect on cognitive classroom readiness. A significant positive effect on self-efficacy was found for intervention group 2. Overall, our research demonstrates the potential of an easy-to-implement online intervention in enhancing self-efficacy and classroom readiness and points towards the importance of combining feedback and reflection within online scenario-based learning activities. Highlights: Study tested online scenario-based learning (SBL) intervention for student teachers. Three conditions with random assignment (SBL, SBL + feedback, SBL + feedback and reflection). Effects on self-efficacy for online SBL condition including feedback and reflection. Effects on cognitive classroom readiness for SBL + feedback and SBL + feedback + reflection conditions. Online scenario-based learning intervention is a useful tool for teacher education.